THE EFFECT OF CORPORATE REPUTATION AND SUSTAINABLE INNOVATION STRATEGY ON BUSINESS PERFORMANCE IN AUTOMOTIVE COMPANIES - Siti Maemunah (Business and Entrepreneurial Review, 2018)
This study aims to determine the effect of company reputation and sustainable innovation strategies on business performance in automotive industry companies in Jakarta. Data obtained by distributing questionnaires to 270 respondents. From 270 data collected, all of them can be analyzed. To analyze data using structural equation modeling (SEM) analysis tools. The results of this study prove that business performance is influenced positively and significantly by the company's reputation and innovation strategy. Business performance is most strongly influenced by the innovation strategy. The limitation of this study was only in Jakarta and four car brands. Further research can be developed with different industries and is expected to add variables that can affect business performance in automotive companies such as customer satisfaction, customer trust and customer relationship management and organizational learning.